Effects of the New Rural Pension Scheme on the Income Distribution in Rural China - Zhenhe Chi (Forest Chemicals Review, 1970)
The study estimates the effects of China’s New Rural Pension Scheme (NRPS) on income distribution using China Household Income Project 2013 data. The results show that the NRPS has an evident effect on income growth and income dispersion in rural China. Average income in rural China increases, especially among the elderly. The NRPS affects income dispersion in two ways. First, it reduces the income gap between the elderly and the youth by raising the elderly’s income. Second, it widens income dispersion through various pension benefits across the 31 provinces. Overall, the narrowing dispersion effect overshadows the widening dispersion effect, leading to reduced income dispersion.